The impact of the COVID-19 pandemic on emergency general surgery: a retrospective study - Tarim, Ismail Alper; Derebey, Murat; Özbalci, Gökhan Selçuk; Özşay, Oğuzhan; Yüksek, Mahmut Arif; Büyükakıncak, Sercan; Bircan, Recep; Güngör, Bahadir Bülent; Başoğlu, Mahmut (São Paulo Medical Journal, 2021)
BACKGROUND: The COVID-19 pandemic has affected healthcare systems worldwide. The effect of the pandemic on emergency general surgery patients remains unknown. OBJECTIVE: To reveal the effects of the COVID-19 pandemic on mortality and morbidity among emergency general surgery cases. DESIGN AND SETTING: Data on patients who were admitted to the emergency department of a tertiary hospital in Samsun, Turkey, and had consultations at the general surgery clinic were analyzed retrospectively. METHODS: Our study included comparative analysis on two groups of patients who received emergency general surgery consultations in our hospital: during the COVID-19 pandemic period (Group 2); and on the same dates one year previously (Group 1). RESULTS: There were 195 patients in Group 1 and 132 in Group 2 (P < 0.001). While 113 (58%) of the patients in Group 1 were women, only 58 (44%) were women in Group 2 (P = 0.013). Considering all types of diagnosis, there was no significant difference between the two groups (P = 0.261). The rates of abscess and delayed abdominal emergency diseases were higher in Group 2: one case (0.5%) versus ten cases (8%); P < 0.001. The morbidity rate was higher in Group 2 than in Group 1: three cases (1.5%) versus nine cases (7%); P = 0.016. CONCLUSIONS: The COVID-19 pandemic has decreased the number of unnecessary nonemergency admissions to the emergency department, but has not delayed patients’ urgent consultations. The pandemic has led surgeons to deal with more complicated cases and greater numbers of complications.